The Results of Surgical Management of Unstable Both-Bone Forearm Fractures in Children - Serbest, Sancar; Tosun, Haci Bayram; Kilic, Sebahattin; Gokce, Halil; Celik, Suat (Derman Medical Publ, 2013)
Aim: In our study; we evaluated the forearm fractures in children which were fixed by intramedullary kirschner wires through close reduction, prospectively. Material and Method: There were two girls and 18 boys who were between 7-14 years with unstable both-bone forearm fractures were prospectively evaluated. Unsuccessfull reduction in seventeen patients, loss of reduction during follow-up in three patients. Results: Union was achieved in all the fractures within a mean of 6,5 weeks (range 6 to 9 weeks). None of the patients developed complications such as deep infection, synostosis, loss of reduction, vessel-nerve-tendon injuries, compartment syndrome, refractures, or implant migration. Pin tract infections seen in two patients were treated with antibiotic treatment. Clinically and radiographically, no length discrepancy was detected between the two forearms. Discussion: Close reduction and intramedullary fixation with kirschner wires is an easy, reliable and alternative method for the forearm fractures in children aged between 7-14 years.
çocuklarda i?nstabil önkol çift kırıklarının cerrahi tedavisi sonuçları
Keywords: Child Forearm Injuries; Fracture Fixation; Intramedullary Methods; Radius Fractures; Ulna Fractures